If the first step in the solution of the equation -8 - 7x = -5x - 10 is "add 10," then what should the next step be? add 7x add 8 add 5x

Skip to content# If the first step in the solution of the equation -8 – 7x = -5x – 10 is ‘add 10,’ then what should the next step be? add 7x add

##
This Post Has 10 Comments

### Leave a Reply

If the first step in the solution of the equation -8 - 7x = -5x - 10 is "add 10," then what should the next step be? add 7x add 8 add 5x

The next step should be ''add 7x''.

Step-by-step explanation:

Given : If the first step in the solution of the equation [tex]-8-7x=-5x-10[/tex] is "add 10,"

To find : What should the next step be?

Solution :

Equation [tex]-8-7x=-5x-10[/tex]

Step 1 - Add 10 both side,

[tex]-8-7x+10=-5x-10+10[/tex]

[tex]-7x+2=-5x[/tex]

Step 2 - Add 7x both side,

[tex]-7x+2+7x=-5x+7x[/tex]

[tex]2=2x[/tex]

Step 3 - Divide both side by 2,

[tex]\frac{2}{2}=\frac{2x}{2}[/tex]

[tex]1=x[/tex]

Therefore, The next step should be ''add 7x''.

-8 - 7x = -5x - 10add 10 to both sides

2 - 7x = -5x NEXT STEPadd 7x to both sides

The next step should be ''add 7x''.

Step-by-step explanation:

Given : If the first step in the solution of the equation [tex]-8-7x=-5x-10[/tex] is "add 10,"

To find : What should the next step be?

Solution :

Equation [tex]-8-7x=-5x-10[/tex]

Step 1 - Add 10 both side,

[tex]-8-7x+10=-5x-10+10[/tex]

[tex]-7x+2=-5x[/tex]

Step 2 - Add 7x both side,

[tex]-7x+2+7x=-5x+7x[/tex]

[tex]2=2x[/tex]

Step 3 - Divide both side by 2,

[tex]\frac{2}{2}=\frac{2x}{2}[/tex]

[tex]1=x[/tex]

Therefore, The next step should be ''add 7x''.

add 7x

Step-by-step explanation:

This would be the answer because if you have already added 10 to the right side of the equation and have erased the constant, you would then need to erase the variable on the other side to make it equal. The variable on the other side is 7x, which gives you the answer.

next step u add 7x

Step-by-step explanation:

its because you need to get x on 1 side when you add the 7x it will be

-2 = 2x

-8 plus the 10 is -2

and -5x plus the 7x is 2

if you need the answer for the equaltion its x = 1

You would add 7x and then finish out the equation

The answer is add 7x.

Step-by-step explanation:

When the first step is to add 10 to both sides :

[tex]- 8 - 7x = - 5x - 10[/tex]

[tex]- 8 - 7x + 10 = - 5x - 10 + 10[/tex]

[tex]- 7x + 2 = - 5x[/tex]

Next, you have to add 7x to both sides to eliminate -7x on the left side :

[tex]- 7x + 2 = - 5x[/tex]

[tex]- 7x + 2 + 7x = - 5x + 7x[/tex]

[tex]2 = 2x[/tex]

-8x-7x=-5x-10

Add or move the -10 to the other side

It becomes: -8+10-7x=-5x

Which then becomes: 2-7x=-5x

Add or move the -7x to the other side

It becomes: 2=-5x+7x

Which then becomes: 2=2x

(I solved it in the picture)

[tex]Choose the answer based on the most efficient method as presented in the lesson. if the first step i[/tex]

Step-by-step explanation:

-8x-7x=-5x-10

Add or move the -10 to the other side

It becomes: -8+10-7x=-5x

Which then becomes: 2-7x=-5x

Add or move the -7x to the other side

It becomes: 2=-5x+7x

Which then becomes: 2=2x

add 7x

Step-by-step explanation:

This would be the answer because if you have already added 10 to one side of the equation and have erased the constant on the right side, you would need to do something to erase the variable on the other side, hence, add 7x. This makes the equation balanced.